Relasi Sosial Penganut Agama Islam Dalam Dinamika Sosial Agama Mayoritas Dan Minoritas - Nur Khalifah Amrinsyah . (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2026)
his study explores the social dynamics and relations between the Muslim majority and the Tolotang minority in Amparita Village, Tellu Limpoe, Sidrap, using a qualitative approach through observation, interviews, and documentation. The findings reveal a harmonious relationship deeply embedded in daily activities, particularly within the economic sector where mutual trust, fair pricing, and cooperation in trade flourish regardless of religious differences. This social cohesion is further strengthened by a culture of mutual respect, where the Tolotang community views the Islamic Adhan as a helpful time reminder, and both groups actively engage in "gotong royong" (mutual cooperation), traditional celebrations, and communal discussions. Ultimately, the integration of honesty, openness, and shared values ensures that religious diversity does not act as a barrier, but rather as a foundation for a peaceful and mutually beneficial communal life.